Story Book Development With Local Culture Content As Learning Companion For 5th Grade Primary Students - Laksmi, Ni Luh Ayu Nitya (International Conference on Elementary Education, 2020)
This study aims to develop children's storybooks supported with local culture as learning companion to continue previous prototype by Kharisma (2017). Method use ADDIE (Analysis, Design, Development, Implementation, Evaluation) which is two first stages already done. Subjects in this study were 2 experts, 2 teachers and 25 students of fifth grade. Development, the process of making the story, and produce a story book entitled "Penyesalan Komang". Implementation, application of storybooks in learning process and evaluation is the results of the implementation of storybook in the classroom. To determine effectiveness seen from reading interest, attitudes, and student learning outcomes. Data collected with questionnaires, reading interest, student attitude observation sheet and learning result test. Data analysis method used descriptive qualitative. Result shows that, (1) Story book entitled "Penyesalan Komang" contains spiritual attitude (obedience of worship,gratitude and behavior), social attitude (honest, responsible, polite, caring, confident), and learning subjects Bahasa Indonesia, PPKn, Mathematics, Science, Social Sciences, SBDP, PJOK and local cultural such as Mebanten Canang s, and Mebanten Saiban. According to the results of expert evaluation, quality and appropriateness of "Penyesalan Komang" is very good. Effectiveness in story book about students' attitude and learning outcomes are very effective, reading interest quite effective